Effect of pentoxifylline on endothelial dysfunction, oxidative stress and inflammatory markers in STEMI patients - Asmaa Saeed; Mohamed Moustafa Farouk; Nagwa Ali Sabri; Mohamed Ayman Saleh; Marwa Adel Ahmed (Future Science OA)
Aim: ST-elevation myocardial infarction (STEMI) patients suffer higher mortality and adverse outcomes linked to endothelial dysfunction (ED). Methods: 43 patients were randomized to pentoxifylline (PTX) 400 mg thrice daily (n = 22) or placebo (n = 21). Soluble vascular cell adhesion molecule-1, malondialdehyde, interleukin-1 (IL-1), interleukin-6 (IL-6), high-sensitivity C-reactive protein (hs-CRP) and tumor necrosis factor-α (TNF-α) were assessed at baseline and 2 months. Results: After 2 months, no significant difference was observed in markers' levels between the 2 groups. However, a within-group comparison revealed a statistically significant change in hs-CRP in the PTX group (10.057 (9.779–10.331) versus 9.721 (6.102–10.191)), p = 0.032. Conclusion: PTX for 2 months in STEMI patients was safe and well-tolerated but had no significant detectable effect on ED, oxidative stress or inflammatory markers.Clinical Trial Registration: NCT04367935 (ClinicalTrials.gov)